Investigating Temporal Variability of Total Ozone Column over Kathmandu Using Omi Satellite Observations - Chapagain, Narayan P. (Journal of Institute of Science and Technology, 2016)
The objective of this work was to analyze the trend of temporal variability of the atmospheric Total ozone column (TOC) over Kathmandu, during the last 13 years of observations using remote sensing-derived data. For this study, long-term TOC data derived from the Ozone Monitoring Instrument (OMI) for the period of October 2004–April 2016 were used. The daily, monthly, seasonal, and annual variations of TOC were analyzed. During the whole study period, the highest value of TOC is found to be 344 DU in March and the lowest value of TOC is 219 DU in December. The average TOC calculated during the whole study period over Kathmandu is found to be 268 DU. The trend of TOC shows a distinct seasonal pattern, with maximum in summer and minimum in winter season, specifically high value in April or May and lower value in December and January. The long-term variability also represents a notable increase in TOC for the period from 2004 to 2015 illustrating the significant recovery atmospheric ozone over Kathmandu. The ozone recovery during the recent years may be due to the reduction of the ozone depletory agents. Journal of Institute of Science and Technology Volume 21, Issue 1, August 2016, Page: 140-147